Coronavirus Disease-19 and Dentistry: A Review - Ali, Fareedi Mukram; Patil, Kishor; Albashir, Elnur Ibrahim; Alamir, Abdulhamid Aidarous (Open Access Macedonian Journal of Medical Sciences, 2020)
Novel coronavirus (nCoV) is a novel form of virus with a new strain identified recently in humans. Common clinical signs and symptoms primarily consist of fever, cough, and breathing difficulties. In severe cases, it can results in pneumonia, severe acute respiratory syndrome, kidney failure, and even death. It is important to follow all infection control measures in prevention of the nCoV from spreading and controlling the epidemic situation. The risk of cross infection can be high between dental practitioners and patients due to the features of dental clinical settings. Here, we are summarizing the nCoV related information and infection control measures to be followed in dental practice.